In Vivo Antihypercholesterolemic Potential of Uncaria cordata (Lour.) Merr as Ethanolic Extract - Meiriza Djohari; Mira Febrina; Tri Wahyuni (Majalah Obat Tradisional, 2021)
The present investigation aims to evaluate the antihypercholesterolemic potential of Uncaria cordata (Lour.) Merr. as an ethanolic extract in diet-induced hypercholesterolemic male white mice model. In this study, white mice were segregated into 6 groups; all the groups except the normal control group were given a high-fat diet to induce hypercholesterolemia. After induction of cholesterolemia, normal and negative control groups were treated with NaCMC, the positive control group was treated with atorvastatin, and the remaining three groups received ethanolic extract Uncaria cordata (Lour.) Merr. in three doses (100, 200, and 400 mg/Kg BW) for a treatment period of 29 days. Measurement of cholesterol levels was performed on days 0, 15, 22, and 29 using EasyTouch® GCU digital devices. The results were analyzed by one way ANOVA test and ANOVA Repeated test. The results showed that the ethanol extract of the Uncaria cordata (Lour.) Merr. root plant dose 100, 200, and 400 mg/Kg BW effect in lowering total cholesterol in male white mice significantly (P <0,05). Ethanol extract from Uncaria cordata (Lour.) Merr. a dose of 200 mg/Kg BW showed a better decrease in cholesterol levels on day 29 compared to day 22.